Joint effects of elevated homocysteine levels and low eGFR on post-stroke cognitive impairment - Chunyan Zhang; Xueqin Cao; Chen Liu; Pengfei Meng; Huizhong Gao; Bo Bai; Cunshui Xue (Frontiers in Neurology)
IntroductionThe correlation between serum homocysteine levels and post-stroke cognitive impairment (PSCI) remains inconsistent. This study aimed to investigate whether serum homocysteine levels are independently associated with PSCI and to assess the effects of renal function on this relationship.MethodsA retrospective analysis was conducted in 608 patients with ischemic stroke. Homocysteine levels were obtained from inpatient medical records, and global cognitive function status 1 month after discharge was assessed using the Mini-Mental State Examination (MMSE) and the Montreal Cognitive Assessment (MoCA). The relationship between homocysteine levels and PSCI was evaluated using univariate and multiple linear and logistic regression analyses.ResultsThe mean age of the patients was 66.6 ± 4.1 years, with 48% being female. The median homocysteine level was 13.8 μmol/L (interquartile range [IQR], 11.3–17.3 μmol/L), and 39.3% of patients had total homocysteine levels above the cutoff of 15 μmol/L. After full adjustment, a stronger positive association between homocysteine levels and PSCI was observed in patients with low estimated glomerular filtration rate (eGFR), with significant interactions between eGFR and MMSE scores (P for interaction = 0.005) and between eGFR and MoCA scores (P for interaction = 0.001). Joint analyses indicated that the highest risk of PSCI was in patients with eGFR < 90 ml/min/1.73 m2 and homocysteine levels ≥15 μmol/L (odds ratios [ORs] were 2.50 [95% CI: 1.49, 4.18; p < 0.001] for MMSE and 13.53 [95% CI: 6.64, 27.56; p < 0.001] for MoCA in the fully adjusted model).ConclusionThese findings highlight the additive value of hyperhomocysteinemia and lower eGFR in predicting incident PSCI risk.